La aplicación de la prueba para mejor resolver en garantía del principio de contradicción - López Bedoya, Luisa Carol (2023)
The research project was based on the theme THE APPLICATION OF THE TEST TO BETTER RESOLVE IN GUARANTEE OF THE PRINCIPLE OF CONTRADICTION, determining within it, the general objective: “Analyze the violation of the principle of contradiction, at the instant of the non-application of the evidence to better resolve in the evidentiary activity”. To meet the objectives, set within the resarch project, the types of documentaries, descriptive, and explanatory resarch approaches, that is, a qualitative approach applied of the ex officio test; quantitative approach, through the surveys carried out to legal professionals in the city of Guayaquil in the area corresponding to this investigation. Obtaining as results the official evidence ordered by the judge, and this is reproduced after the initial argument, his evidence would violate the right to equal procedural, due process and the principle of contradiction since it could not be contradicted since we would be outside the evidentiary debate, said evidence would enter without any evidentiary control.